2010
DOI: 10.1111/j.1439-037x.2009.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

PEP‐Carboxylase Activity: A Comparison of its Role in a C4 and a C3 Species Under Salt Stress

Abstract: In our experiments, we found an increase of PEP‐carboxylase activity in young shoots of maize under salt stress. Within this study, several analyses were carried out to identify the function of this enhanced enzyme activity during salt stress. In our first experiment, we analysed plants of the salt‐resistant maize hybrid SR 03 (Zea mays L.), whereas in the second experiment, we compared maize and wheat (Triticum aestivum L. cv. Thasos), which were grown under two different light intensities for 20 days. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…This allows C 4 plants to improve its light absorption efficiency and its photo-assimilate production (Hatzig et al, 2010). Maize physiological response to both row spacing and high planting density was positive in relation to other treatments resembling the results of some authors (Maddonni et al, 2001;Blumenthal et al, 2003;Berzsenyi and Tokatlidis, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…This allows C 4 plants to improve its light absorption efficiency and its photo-assimilate production (Hatzig et al, 2010). Maize physiological response to both row spacing and high planting density was positive in relation to other treatments resembling the results of some authors (Maddonni et al, 2001;Blumenthal et al, 2003;Berzsenyi and Tokatlidis, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Measurements were made during 13:00-14:00 h local time. 1975; Amzallag et al, 1990;Hatzig et al, 2010). Hatzig et al (2010) suggested that the enhancement of PEPCase activity supported organic acid metabolism since the malate concentration in salt-treated plants was little or not decreased in comparison with control.…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that activities of C 4 photosynthetic enzymes localized in MC chloroplasts may be more affected under salt condition than those in BSCs, and therefore photosynthetic rate and products become restricted. The effect of salinity on PEPCase which localizes in the mesophyll cytosol has been investigated in several NADP-ME type C 4 species, and most studies showed that PEPCase activity increased in salt-treated plants (Sankhla and Huber, 1975;Amzallag et al, 1990) while it was little changed by salinity in aged maize leaves (Hatzig et al, 2010). Meanwhile, little is known how salinity affects other key enzymes which are involved in NADP-ME type C 4 photosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Inoculated plantlets were transferred to sterile rubber plugs (1.7 cm, 2 cm length), with a central hole of approximately 0.5 cm, placing the root system at the lower part of rubber plug to protect it from light influence, and immediately sealed with sterile agar 1.5% (50 C). Four rubber plugs with the fixed plantlets were transfer to round grey plastic racks (4.5 cm diameter  3 cm depth) and placed in sterile transparent plastic boxes (9.5  8.0  12 cm) filled with 175 ml of half concentrated plant nutrient solution (Hatzig et al, 2009) adjusted to a final 1% NaCl concentration in order to both generate the salt stress to the plantlets and maintain the optimal NaCl concentration for the growth of strain E19 T . The boxes were placed in greenhouse for 8 days under the same conditions described above.…”
Section: Bacterial Detection Of H Diazotrophicus By Fish In Plant Rootsmentioning
confidence: 99%